2019
DOI: 10.1007/s00726-019-02719-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of polyamines in the regulation of macrophage polarization and function

Abstract: Naturally occurring polyamines are ubiquitously distributed and play important roles in cell development, amino acid and protein synthesis, oxidative DNA damage, proliferation, and cellular differentiation. Macrophages are essential in the innate immune response, and contribute to tissue remodeling. Naïve macrophages have two major potential fates: polarization to 1) the classical pro-inflammatory M1 defense response to bacterial pathogens and tumor cells, or 2) the alternatively-activated M2 response, induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 75 publications
(152 reference statements)
2
85
0
6
Order By: Relevance
“…Indeed, for NOS2, both IL1B and TNFA expression in the bowel were independent predictors of NOS2 expression, although while the correlation with IL1B was positive, it was negative in the case of TNFA. Interestingly, the association was tighter in quiescent and non-inflamed tissue, although tissue healing and remodeling are associated with M2 macrophages, characterized by an upregulated ARG1/2-ODC1 pathway and polyamine synthesis [59]. Therefore, one might expect a positive correlation between ARGs and ODC1 in quiescent tissue.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, for NOS2, both IL1B and TNFA expression in the bowel were independent predictors of NOS2 expression, although while the correlation with IL1B was positive, it was negative in the case of TNFA. Interestingly, the association was tighter in quiescent and non-inflamed tissue, although tissue healing and remodeling are associated with M2 macrophages, characterized by an upregulated ARG1/2-ODC1 pathway and polyamine synthesis [59]. Therefore, one might expect a positive correlation between ARGs and ODC1 in quiescent tissue.…”
Section: Discussionmentioning
confidence: 96%
“…Kolios et al [58] reported that epithelial cells are the main source of NOS2 in inflamed colon. However, NOS2 up-regulation is a hallmark of M1 macrophages and is accompanied by increased expression and secretion of proinflammatory cytokines, that is, IL1β, TNFα, and IL-12 [59]. Indeed, for NOS2, both IL1B and TNFA expression in the bowel were independent predictors of NOS2 expression, although while the correlation with IL1B was positive, it was negative in the case of TNFA.…”
Section: Discussionmentioning
confidence: 97%
“…However, the phagocytic capacities of these cells were diminished in chronic inflammatory disorder. 39,40 Efferocytosis, the process by which apoptotic cells are taken up and removed, is generally considered to be a function of M2 macrophages. [41][42][43] M2 macrophages are also characterized by high expression of the mannose receptor CD206 and scavenger receptor CD163, which assist in apoptotic cell recognition and endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, serine/threonine kinases, which were enriched in spermidine-treated cells, are known to phosphorylate Akt among other proteins ( Burgering and Coffer, 1995 ). Spermidine as a polyamine has been shown to mimic the effect of Ca 2+ activation ( Koenig et al, 1983 ; Toninello et al, 2004 ), modulate immune responses ( Latour et al, 2020 ; Theoharides, 1980 ) and trigger phagocytosis ( TranVan Nhieu et al, 2004 ). Furthermore, polyamine depletion has previously been shown to result in increased expression of LPS-induced proinflammatory genes, coinciding with our findings of an enhanced production of TNF-α and IL-6 in the motility mutants ( Van den Bossche et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%